2010
DOI: 10.1001/archgenpsychiatry.2010.117
|View full text |Cite
|
Sign up to set email alerts
|

Biological Validation of Increased Schizophrenia Risk With NRG1, ERBB4, and AKT1 Epistasis via Functional Neuroimaging in Healthy Controls

Abstract: CONTEXT NRG1 is a schizophrenia candidate gene and plays an important role in brain development and neural function. Schizophrenia is a complex disorder, with etiology likely due to epistasis. OBJECTIVE We sought to examine epistasis between NRG1 and selected NMDA-glutamate pathway partners implicated in its effects, including ERBB4, AKT1, DLG4, NOS1, NOS1AP. DESIGN Schizophrenia case-control sample analyzed using machine learning algorithms and logistic regression with follow-up using neuroimaging on an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
76
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 59 publications
0
76
1
Order By: Relevance
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…Titles and abstracts were scrutinized to exclude non-genetic studies, reducing the number of included studies to Costain et al, 2010;Fang et al, 2008;Greenwood et al, 2011;Husted et al, 2010;Kremeyer et al, 2009;Miranda et al, 2006;Nicodemus et al, 2008;Wratten et al, 2009) and one on NOS1 (Fallin et al, 2005), presented family-based, but not case-control data and were therefore not integrated in the meta-analysis for methodological reasons. The remaining studies on NOS1AP (n=6; (Aberg et al, 2010;Delorme et al, 2010;Nicodemus et al, 2010;Puri et al, 2007;Puri et al, 2006;Zheng et al, 2005)) and NOS1 (n=14; (Cui et al, 2010;Donohoe et al, 2009;Kawohl et al, 2008;Nicodemus et al, 2010;O'Donoghue et al, 2012;Okumura et al, 2009;Reif et al, 2006;Reif et al, 2011;Riley et al, 2010;Rose et al, 2012;Shinkai et al, 2002;Silberberg et al, 2010;Tang et al, 2008;Wang et al, 2012)) reported on case-control association data and were scrutinized in greater detailed. For NOS1AP, two and for NOS1, 11 further studies had to be excluded from meta-analysis for the following reasons.…”
Section: Meta-analysismentioning
confidence: 99%
“…For the NOS1 gene: (Kawohl et al, 2008;O'Donoghue et al, 2012;Rose et al, 2012) analysed exclusively healthy participants. (Donohoe et al, 2009;Nicodemus et al, 2010;Riley et al, 2010) and (Shinkai et al, 2002) only presented data on SNPs which have not been genotyped for the present study; no SNP data could be obtained from the study of (Wang et al, 2012); and the study by (Silberberg et al, 2010) was excluded because of the rather small sample size (n=26) precluding meaningful interpretation of the data. Finally, (Reif et al, 2011) and (Reif et al, 2006), were excluded because the case samples of both studies overlapped with the sample described here (while the control sample was extended more than two-fold).…”
Section: Meta-analysismentioning
confidence: 99%
See 3 more Smart Citations